PENGARUH NILAI BUKU, ECONOMIC VALUE ADDED, DAN RETURN ON ASSET TERHADAP RETURN SAHAM - Venni Suryani Senohadi; Perminas Pangeran (Jurnal Riset Manajemen dan Bisnis, 2014)
This study aimed to examine the effect of the financial performance on banking’s stock return. The study was conducted on 22 banking companies listed in Indonesia Stock Exchange for the period of 2007 to 2009. The results showed that the Return on Assets (ROA) has a positive impact on stock returns. Likewise, Economic Value Added (EVA) has a positive effect on stock returns. Nevertheless, book value (BV) has no effect on stock returns Keywords: Stock Return, Economic Value Added, Return on Assets, Book Value.